Specialty Payment Model Opportunities and Assessment Oncology Simulation Report - White, Chapin (RAND Corporation, 2015)
This report describes the results of a simulation analysis of a payment model for specialty oncology services that is being developed for possible testing by the Center for Medicare and Medicaid Innovation at the Centers for Medicare & Medicaid Services (CMS). CMS asked MITRE and RAND to conduct simulation analyses to preview some of the possible impacts of the payment model and to inform design decisions related to the model.